2021
DOI: 10.31330/penamas.v34i1.389
|View full text |Cite
|
Sign up to set email alerts
|

Persekusi Vesus Egaliter Lokalitas Masyarakat Sumatera Barat

Abstract: The philosophy of “Adat Basandi Syara’ and Syara Basandi Kitabullah (ABSSBK)” held firmly by West Sumatra people was affected by the persecution by a group of people. The collapse of adat (custom) as a cultural basis for the Minang people is due to the strengthening of identity politics and the poor understanding of society to the role of the media. The purpose of this research is to uncover and analyze the phenomenon of the strengthening the identity politics in the aftermath of 212 actions and its influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…35 to 60 percent of pregnant women have back pain. It was found that 47-60% of pregnant women reported having back discomfort between the first and fifth months of their pregnancies (Putri & Kusumastusti, 2021). Furthermore, more than 50% of pregnant women in the United States, Canada, Iceland, Turkey, Korea, and Israel also reported having back pain (Suryani & Ina Handayani, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…35 to 60 percent of pregnant women have back pain. It was found that 47-60% of pregnant women reported having back discomfort between the first and fifth months of their pregnancies (Putri & Kusumastusti, 2021). Furthermore, more than 50% of pregnant women in the United States, Canada, Iceland, Turkey, Korea, and Israel also reported having back pain (Suryani & Ina Handayani, 2018).…”
Section: Introductionmentioning
confidence: 99%